Analog integrated circuit design / Tony Chan Carusone, David A. Johns, Kenneth W. Martin. - Carusone, Tony Chan (Wiley, 2013)
The discussion of professional applications and the use of real-life circuit design examples make this text a useful tool for both undergraduate and graduate students preparing for circuit design on a professional level.